Look at this expression, and complete the statements.
3x + 2(x + 2) + 4
In the first term, 3 is
In the second term, (x + 2) is
In the last term, 4 is

Respuesta :

Answer:

[tex]3 \to[/tex] Coefficient of x

[tex](x+2)\to[/tex] Variable

[tex]4 \to[/tex] Constant

Step-by-step explanation:

Given

[tex]3x + 2(x +2) + 4[/tex]

Required

Complete the statements

In 3x, x is the variable; so:

[tex]3 \to[/tex] Coefficient of x

In 2(x + 2), 2 is the variable so:

[tex](x+2)\to[/tex] Variable

4 stands alone. So, it is a constant

[tex]4 \to[/tex] Constant